Gamification usage ecology - Costa, C. J.; Aparicio, M.; Aparicio, S.; Aparicio, J. T. (35th ACM International Conference on the Design of Communication, 2017)
Gamification is applied in academia and industry and is being studied in the last years. Gamification is nowadays applied to several areas, such as learning, computer science, business, marketing, tourism, among others. However, we need to understand to what extent it is studied in academic context. We present a bibliographic study on gamification research, by identifying publications trends. This paper presents the gamification related areas, result from a publication keyword analysis of the scientific publications on gamification. In this paper, we also identify the game elements, game mechanics, and game dynamics, used as part of any gamification implementation. In this study are also present the most used gamification theoretical models.